A Microsimulation Approach to the Modelling of Urban Population and Housing Markets Within an Object-Oriented Framework - Marianthi Svinterikou; Pavlos Kanaroglou (European Regional Science Association (ERSA), 2006)
The structure of a city constantly changes, in accordance to the population's housing demand and the city's housing supply. Housing demand depends on several factors, such as changes in household structure caused by demographic events (e.g. mortality, fer
Keywords: 330